PENGARUH INTEGRASI SISTEM INFORMASI INTERNAL,INTEGRASI SISTEM INFORMASI EKSTERNAL,MANAJEMEN BIAYA INTERNAL DAN KAPASITAS DAYA SERAP TERHADAP MANAJEMEN BIAYA ANTAR ORGANISASI DALAM RANTAI PASOKAN(STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI PROVINSI BANTEN) - Galih Fajar Muttaqin; Imam Abu Hanifah; Rika Andrawulan (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This study aimed to examine the effect of Internal Information Systems Intregation, External Information Systems Intregation integration, Internal Cost Management and Absorptive Capacity on inter-organizational cost management in supply chains. Of the 84 questionnaires distributed, the number of questionnaires returned was 36 questionnaire (42,86%). The data is processed by using Structural Equation Modeling (SEM) by using a software program Partial Least Square (PLS) Verion 2.3.7. This study was conducted in Manufacturing company located in Banten province, with the Respondents in this study are financial managers, production managers, and marketing managers. This study uses survey research with primary data collection using the questionnaire.